Tuberculous osteomyelitis of the mandibular condyle: A rare case report and review of the literature (Indian Journal of Case Reports, 2021)
Tuberculosis (TB) is a chronic infectious granulomatous disease caused by the air-borne bacillus Mycobacterium tuberculosis and less frequently by other bacteria in the M. tuberculosis complex (Mycobacterium Bovis and Mycobacterium africanum). Tuberculous osteomyelitis of the condyle may present atypical clinical findings akin to temporomandibular joint arthritis or middle ear infections. A detailed clinical and radiographic examination aided by a histopathological and a microbiological diagnostic workup is the key to timely detection and administration of appropriate therapeutic regimens. A high degree of clinical suspicion is thus advocated in patients with such atypical presentations. We, hereby, are presenting a rare case of tuberculous osteomyelitis in a 15-year-old female child.